1998
DOI: 10.1007/s004410051206
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular effects and localization of binding sites of phytohemagglutinin in the potato leafhopper, Empoasca fabae (Insecta: Homoptera: Cicadellidae)

Abstract: To identify the means by which phytohemagglutinin (PHA) exerts its toxicity on the potato leafhopper, four different methods (thick and semi-thin sectioning combined with immunofluorescent staining, in vitro receptor autoradiography, and immunoelectron microscopy) were used to elucidate the PHA target tissue, binding site, and its effects on this tissue. Sixteen 1- or 2-day-old female potato leafhoppers were fed for 36 h on each of three treatments: a control, diet or a diet containing either the PHA-E subunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…The current study did not measure the effects of PHA on insect development and fecundity. Other studies, however, have demonstrated that PHA can reduce the growth and fecundity and can increase the mortality of herbivorous insects (Gatehouse et al 1984;Rahbe et al 1995;Habibi et al 1998;Machuka et al 1999;Sadeghi et al 2006;Sprawka and Leszczyński 2007). The results presented here suggest that the negative effects of PHA on herbivorous insects, and especially aphids, could be a consequence of shortening or suppressing of feeding processes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The current study did not measure the effects of PHA on insect development and fecundity. Other studies, however, have demonstrated that PHA can reduce the growth and fecundity and can increase the mortality of herbivorous insects (Gatehouse et al 1984;Rahbe et al 1995;Habibi et al 1998;Machuka et al 1999;Sadeghi et al 2006;Sprawka and Leszczyński 2007). The results presented here suggest that the negative effects of PHA on herbivorous insects, and especially aphids, could be a consequence of shortening or suppressing of feeding processes.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have also shown the toxic effect in vitro or in planta of lectins to different species of Hemiptera: leafhoppers, planthoppers, and aphids (Habibi et al 1993;Powell 1993Powell , 2001Powell et al 1993Powell et al , 1995Powell et al , 1998Rahbe and Febway 1993;Rahbe et al 1995;Sauvion et al 1996). Previous studies on a number of economically important pests have indicated that the kidney bean lectin (Phaseolus vulgaris agglutinin) phytohemagglutinin (PHA) had the most interesting toxic effects of all classes of lectins tested (Fitches et al 2001;Habibi et al 1998Habibi et al , 2000Machuka et al 1999;Rahbe et al 1995;Sadeghi et al 2006;Sprawka and Leszczyński 2007). PHA is tetrameric protein with a molecular weight of 120 kDa and sugar specificity for D-galactose/N-acetyl-D-galactosamine residue.…”
Section: Introductionmentioning
confidence: 96%
“…Tissues were prepared at the 2-, 4-, and 8-h time points (Habibi et al, 1998(Habibi et al, , 2000. The control and treatment insects were fixed in 3% paraformaldehyde, dehydrated in a series of ethanol dilutions, infiltrated with low melting paraplast, and embedded in high melting paraplast.…”
Section: Tissue Preparation For Immunohistochemical Detection Of Gfpmentioning
confidence: 99%
“…In general, the action mechanism of the lectin at cellular level of ingested lectin by insects showed that binding of the lectin to the midgut tract causing disruption of the epithelial cells including elongation of the striated border microvilli, swelling of the epithelial cells into the lumen of the gut lead to complete closure of the lumen, permeability of cell membrane to allow the harmful substances penetrations from lumen towards haemolymph and impaired nutrient assimilation by cells, allowing absorption of potentially harmful substances from lumen into circulatory system, fat bodies, ovarioles and throughout the haemolymph (Gatehouse et al, 1984;Powell et al, 1998;Habibi et al, 1998;2000;Fitches et al, 1998;2001b;Sauvion et al, 2004;Majumder et al, 2005). This information gave further support to previous suggestions that the XCL lectins disrupt midgut cells (Francis et al, 2003;Karimi et al, 2008Karimi et al, , 2009).…”
Section: Action Mechanism Of Lectin At the Tissue Level Of Insectsmentioning
confidence: 99%